Analyzing the technical and allocative efficiency of small-scale maize farmers in Tzaneen Municipality of Mopani District: a cobb-douglas and logistic regression approach - Mokgalabone, M.S. (University of Limpopo, 2015)
Agriculture plays an important role in uplifting the economy of South Africa. Small-scale farmers in rural areas are linked with poverty and operate inefficiently due to over or under utilization of some of the factors of production. This study aimed at analysing the technical and allocative efficiency of small-scale maize farmers in Tzaneen municipality. The objectives of the study were: (i) To assess the level of technical and allocative efficiency of small-scale maize farmers in Tzaneen municipality, (ii) To identify socio-economic factors affecting the efficiency of small-scale maize farmers in Tzaneen municipality and (iii) to investigate the areas of improvement with regard to the operational management of the small-scale maize farmers in Tzaneen municipality. The study employed the Cobb-Douglas production function and the logistic regression model to analyse data. The Cobb-Douglas production function results revealed that small-scale maize farmers in Tzaneen municipality are technically efficient in the production of maize with the highest mean technical efficiency value of 0.71%. The study further revealed that farmers were allocatively inefficient with a mean allocative efficiency value of 0.39%. The logistic regression analysis revealed important variables such as the level of education (1.05), experience in farming (2.74), access to irrigation water (0.59), purchase of hybrid seed (0.74), access to credit (2.13) and extension visits (0.85) were positively significant towards the efficiency of farmers. Variables such as gender of the farmer (-1.79) and off-farm income (-2.72) were found to be negatively significant towards the efficiency of small-scale maize farmers in Tzaneen Municipality. The findings obtained in this study could be quite useful to policy makers. This study recommend that there is a need for more visits from the extension officers as well as training on inputs allocation, since variables like Seed (0.41), fertilizer (0.17), capital (0.71) and expenses (-0.204) were found to be inefficiently allocated in the production of maize. The provision of easy, quick and adequate credit deserves to be a top priority on the agenda of policy makers since most small-scale maize farmers in Tzaneen municipality does not receive off-farm income. Small-scale farmers in Tzaneen municipality also need to have access to enough arable land in order to increase production. Small-scale farmers in South Africa and other developing countries contribute to employment creation and food security in the households, therefore, it is important that government fully support such farmers.
Thesis (M.Sc (Agricultural Economics)) --University of Limpopo, 2015
Keywords: Small scale farmers; Socio-economic factors; Agricultural technical efficiency; 338.180968; Rural development projects -- South Africa; Farmers -- Economic conditions